2022
DOI: 10.1186/s13148-022-01301-y
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation: a potential mediator between air pollution and metabolic syndrome

Abstract: Given the global increase in air pollution and its crucial role in human health, as well as the steep rise in prevalence of metabolic syndrome (MetS), a better understanding of the underlying mechanisms by which environmental pollution may influence MetS is imperative. Exposure to air pollution is known to impact DNA methylation, which in turn may affect human health. This paper comprehensively reviews the evidence for the hypothesis that the effect of air pollution on the MetS is mediated by DNA methylation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 140 publications
0
15
0
Order By: Relevance
“…Exposure to several air pollutants, including particulate matter, ozone, nitrogen dioxide, and polycyclic aromatic hydrocarbons, has been found to be positively associated with the risk of MetS [25][26][27][28][29]. As a common type of air pollutant, the associations of VOC exposure with MetS and its components need to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to several air pollutants, including particulate matter, ozone, nitrogen dioxide, and polycyclic aromatic hydrocarbons, has been found to be positively associated with the risk of MetS [25][26][27][28][29]. As a common type of air pollutant, the associations of VOC exposure with MetS and its components need to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…358 In addition, air pollution may lead to metabolic syndrome through DNA methylation changes. 359 Interactions between genetics and epigenetics in metabolic diseases Genetics is a pivotal factor in the development of metabolic diseases. Twin and adoption studies and linkage analyses have provided an abundance of evidence on the role of genetics.…”
Section: Interactions Between Nongenetic Risk Factors and Epigenetics...mentioning
confidence: 99%
“…Accumulating clinical studies and basic experiments have identified the positive associations between PM 2.5 and oxidative stress, systemic proinflammation modification as well as insulin resistance, which may consequently increase the risk of various chronic cardiometabolic diseases [10]. Furthermore, experimental research has highlighted that PM 2.5 could induce cell death via different molecular patterns and multiple signaling pathways [11]. Therefore, studies for evaluating the association between long-term PM 2.5 exposure and the risk of MetS draw much attention in recent years [12,13].…”
Section: Introductionmentioning
confidence: 99%